Qualitative Analysis Of The Coastal Strip South Of The Caspian Sea Waters And Determine Environmental Health Indicators In Coastal Projects Of Guilan - Ramin Nabizadeh; Masoud Binesh Brahmand; Kazem Naddefi; Ali Reza Mesdaghiniya (سلامت و محیط, 2012)
Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 Background and Objectives: Guilan province, with unique environmental values ​​of the Caspian Sea is located in the southwest of Caspian Sea. Disposal of untreated domestic sewage, industrial and agricultural surface water cause pollution of the Caspian Sea region and endanger the health of swimmers. This study performed to determine the microbial contamination of coastal water in Guilan. Materials and Methods: In this work, 21 sampling point in the Caspian Sea littoral provinces of Guilan were selected and microbial contaminations were assessed using microbial indicators of fecal and total coliform. Parameters such as pH, temperature, and turbidity also monitored during the year. In this study, 122 samples were taken and then analyzed by statistical software. Results: The results showed that the average values of total coliform and fecal coliform were 234.8 and 60 MPN per 100 ml, respectively. The fecal pollution appeared to be high in some stations. Also significant relationship between temperature, turbidity and microbial contamination was observed (P< 0.05). Conclusion: The results revealed high total coliform in the two stations. The average fecal coliform of six stations were higher than the local standards. st1":*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;}